Capital structure in the developed world: The roles of firm- and country-specific determinants - FU, LEI (2015)
This paper analyzes the importance of firm-specific and country-specific factors in the leverage choice of listed firms from developed countries. The analysis yields three new results. First, this study finds that firm-specific and macro-economic determinants of leverage differ across countries, only the Tangibility shows significant impact on leverage in all eight developed countries. Second, the results of firm-specific and macro-economic analysis imply that the Pecking Order theory is the most appropriate theory to explain the financial behavior of firms in developed countries. Third, this study proves that legal system plays an important role in the financial decision of listed firms in developed countries. The differences in legal system have significant impact on the leverage ratio.